Next steps in parenting the child who hurts : tykes and teens - Archer, Caroline, 1948- (Jessica Kingsley Publishers, 1999)
Caroline Archer sets out to provide adoptive and foster parents with an understanding of the complex range of difficulties with which their children may struggle as a result of their early experience of adversity. She presents strategies to help parents deal with their youngsters' troubling behaviour, in what seems to them a hostile world.